Letter to Jane Tolmach from Marcia Herman and Mary Aidlin - Marcia Herman::::::; Mary Aidlin:::::: (1976)
In a letter dated March 17, 1976, the non-partisan volunteer organization WOMEN FOR: wrote to Jane Tolmach of Oxnard, California. The group described itself as representing Southern California women active in education, legislation, conservation, health, welfare, and peace. It explained that it supports selected candidates and ballot measures aligned with its values. To assist in making endorsements for the 1976 primary elections, the organization requested information about the issues in her race, her positions, biographical background, and campaign materials. The letter concluded by stating that the Politics Committee would review the materials and contact her if an interview was warranted.